(untitled) (المجلة الدولية للبحوث العلمية, 2023)
This paper is interested in proposing a set of proposed practices for eXtreme Programming (XP) approach to improve the quality of applying this approach in the domain of the software development process. This paper clarifies the basic concepts of agile methods and presents the fundamentals and features of XP approach. life cycle phases of XP approach include six phases: exploration, planning, iterations to release, production, maintenance, and death. Each XP phase can be achieved through performing a set of activities or steps. The researchers developed a set of improved steps for achieving XP phases. The researchers also propose a quality assurance approach for applying XP approach. The proposed quality assurance approach can be used for assuring the quality of achieving XP phases. Then, the deviation between the actual quality and the acceptable quality level can be identified and analyzed. The weaknesses of the software development practices can be discovered, treated to improve the quality of each phase, and avoided in further phases. The strengths of the proposed practices are utilized to increase the quality of achieving the software projects.